2018
DOI: 10.1021/acs.orglett.8b03016
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Chemoselective Protodecarboxylation of Polyenoic Acids

Abstract: Conditions for the first palladium-catalyzed chemoselective protodecarboxylation of polyenoic acids to give the desired polyenes in good yields are presented. The reactions proceed under mild conditions using either a Pd(0) or Pd(II) catalyst and tolerate a variety of aryl and aliphatic substitutions. Unique aspects of the reaction include the requirement of phosphines, water, and a polyene adjacent to the carboxylic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…[28] Hydrocarboxylation of 3y gave naproxen,anonsteroidal anti-inflammatory drug. This is in line with Croatt's mechanistic proposal fort he Pd/phosphine-catalyzedp rotodecarboxylation of polyenoic acids, [24] which involves ar eversible Michael addition of the phosphine to the unsaturated carboxylates. The kinetic profile of the vinylation of 1a showed that the substrates are rapidly consumed and that the postulated cinnamic acid intermediate 4a builds up in solution Scheme2.Mechanistic outline for the envisioned processes.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…[28] Hydrocarboxylation of 3y gave naproxen,anonsteroidal anti-inflammatory drug. This is in line with Croatt's mechanistic proposal fort he Pd/phosphine-catalyzedp rotodecarboxylation of polyenoic acids, [24] which involves ar eversible Michael addition of the phosphine to the unsaturated carboxylates. The kinetic profile of the vinylation of 1a showed that the substrates are rapidly consumed and that the postulated cinnamic acid intermediate 4a builds up in solution Scheme2.Mechanistic outline for the envisioned processes.…”
supporting
confidence: 88%
“…The key requirements of an effective catalytic system for the desired transformation were identified to be that it 1) is just active enough to catalyze the vinylation reaction with acrylic acid, 2) does not mediate any further coupling of the aryl bromide with styrenes or cinnamic acids, 3) effectively promotes the protodecarboxylation of cinnamic acids but not that of acrylic acid, and 4) operates under sufficiently mild conditions to avoid undesired oxidation or polymerization of substrates and/or products. Ideally, the decarboxylation would be promoted by the same palladium catalyst that mediates the cross‐coupling step …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quite interestingly, during the substrate scope investigation, a by-product 9-2 from the decarboxylation of 1-11 was isolated in 9% yield, evoking our suspension that this reaction might follow the "Decarboxylation-Heck type" mechanism. However, the background reaction without adding substrate 2-24 failed to yield any decarboxylation product 9-2, while~70% starting material 1-11 remained untouched 33 (Fig. 7c; Supplementary Fig.…”
Section: Possible Reaction Mechanismsmentioning
confidence: 99%